(untitled) (CIPEEX, 2024)
The World Health Organization (WHO) set the theme of Safe Surgery Saves Lives as an objective to be achieved in surgical centers. In this context, the multidisciplinary approach intertwined under the parameters of effective interpersonal communication, safe techniques and procedures, costs and risks, infection control, surgical safety checklist, among others, establishes itself as a foundation in reducing adverse events in the light of medicine based on evidence and their respective satisfactory results. To analyze the importance of Safe Surgery and its outcomes in surgical centers, based on evidence from the implementation of the global guideline Safe Surgery Saves Lives. The study is a literature review based on the guiding question about Safe Surgery Saves Lives with a focus on evidence-based Medicine 20 articles were analyzed, in which 5 articles published in the last 5 years were chosen to study the topic in the PubMed database. The present studies demonstrated that the campaign based on simple methods proved to be effective and promising when used well, for example, there was a 33% reduction in potentially lethal adverse events when applying the surgical checklist. Thus, proving to be an indispensable tool when managing the patient’s well-being before, during and after the surgical procedure. The results showed that simple interprofessional interventions in the health care environment, which in addition to being complex, deals with human lives and possible events related to the disease itself, as well as less safe practices in surgical procedures can lead to harm to the patient. Therefore, a systemic approach is necessary that understands the need to use the simple t understand the entire process and ensure well-elucidated practices and ensure patient safety.